E-008 Endovascular recanalization of intracranial arterial stenosis in patients with medical failure. (23rd July 2017) - Aguilar-Salinas, P; Hanel, R; Sauvageau, E; Lopes, D; Saied, A; Jovin, T; Jadhav, A; Kaustubh, L; Brasiliense, L; Dumont, T; Cherian, J; Kan, P; et al.
Abstract : Introduction: The optimal management of intracranial arterial stenosis is unclear in particular in patients who have failed medical management. We now report a multicenter experience of endovascular recanalization of intracranial artherosclerotic stenosis refractory to medical therapy. Methods: Retrospective multicenter case series of consecutive endovascularly treated patients presenting with symptomatic (TIA or stroke) who have failed medical therapy. All of the patients were considered to be in the high-risk category with unstable symptomatic intracranial stenosis and progression or recurrence of their symptoms despite the best medical management who required endovascular intervention either with stenting and/or balloon angioplasty. Results: Fifty patients presented with recurrent TIAs (n=26) or strokes (n=24) were treated in 5 stroke centers from 2011 to 2017. All patients underwent best medical management in the decision of the stroke neurologist and were enroll in this study only if they had recurrent or progression of symptoms despite their medical therapy. The majority of lesions were located in the M1 segment (15/50). There was one periprocedural vessel perforation resulting in patient death, one case of groin hematoma, one intraprocedure hemorrhage, and one periprocedural stroke. Twelve patients (24%) had restenosis on follow up imaging and 80% (33/41) of patients were symptom free at 90 day follow-up. Three patients had a stroke in the territory of the stenosis and 5 patients had recurrent TIAs. Conclusion: Endovascular recanalization of unstable intracranial atherosclerotic stenosis who have failed medical therapy is feasible and safe. Disclosures: P. Aguilar-Salinas: None. R. Hanel: 1; C; Microvention. 2; C; Medtronic; Stryker; Microvention. 4; C; Blockade Medical. E. Sauvageau: None. D. Lopes: 2; C; Microvention. A. Saied: None. T. Jovin: 2; C; Medtronic. 3; C; Blockade Medical; Silk Road Medical. A. Jadhav: None. L. Kaustubh: None. L. Brasiliense: None. T. Dumont: None. J. Cherian: None. P. Kan: None. A. Aghaebrahim: None.